Pengaruh Kualitas Sistem, Kualitas Informasi dan Kualitas Layanan terhadap Kepuasan Pengguna Aplikasi Grab di Kelurahan Silalas Medan - Helmi, M. Haivan; Syahputri, Yuni (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The study aims to determine and analyze the effect of system quality, information quality, and service quality on user satisfaction with the Grab application in Silalas Village Medan. The type of research used in this study is quantitative research, with the types of data use being primary and secondary data. The population of this study was the entire community in Silalas Village, which consisted of 8,155 people, with a sample size of 99 respondents. The sampling technique used was puposive sampling, and the data analysis method used was descriptive analysis. Data collection was carried out using questionnaires, and the data was processed using the SPSS program. The result of the study show that (1) System quality has a positive and significant effect on user satisfaction with a t-value of 3,524 > t-table 1,985. (2) Information quality has a positive and significant effect on user satisfaction with a t-value of 2,881 > t-table 1,985. (3) Service quality has a positive and significant effect on user satisfaction with a t-value of 2,763 > t-table 1,985. (4) System quality, information quality, and service quality simultaneously have a positive and significant effect on user satisfaction with the Grab application in Silalas Village Medan with an f-value of 22,562 > t-table 2,70.